A fast and robust approach to compute nonlinear Fluid-Structure Interactions on yacht sails – Application to a semi-rigid composite mainsail. (1st April 2020) - Sacher, Matthieu; Leroux, Jean-Baptiste; Nême, Alain; Jochum, Christian
Abstract: A numerical method to compute the nonlinear Fluid-Structure Interactions (FSI) of yacht sails is presented in this paper. The inviscid lifting-line flow model is used by including a quadrature method to efficiently compute sail pressure loads. The structural calculation is performed with a quasi-static resolution by using a dynamic backward Euler scheme, in order to improve the computation convergence. A specific thickness sail approach is also proposed to make the FSI solving easier. The assembly of these flow and structural methods leads to a fast and robust strategy to compute nonlinear FSI on yacht sails, and the proposed approach is applied on a complex semi-rigid composite mainsail. Highlights: An inviscid lifting-line flow model is used by including a quadrature method to efficiently compute sail pressure loads. A specific thickness sail approach is proposed to make the FSI solving easier. The assembly of flow and structural methods leads to a fast and robust strategy to compute nonlinear FSI on yacht sails. Methods are applied on a complex semi-rigid composite mainsail.